2005
DOI: 10.1128/mcb.25.6.2117-2129.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and Functional Characterization of PC2 and RNA Polymerase II-Associated Subpopulations of Metazoan Mediator

Abstract: The coactivator complexes TRAP/SMCC and PC2 represent two forms of Mediator. To further understand the implications of the heterogeneity of the cellular Mediator populations for regulation of RNA polymerase II (Pol II) transcription, we used a combination of affinity and conventional chromatographic methods. Our analysis revealed a spectrum of complexes, including some containing significant proportions of Pol II. Interestingly, the subunit composition of the Pol II-associated Mediator population resembled tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
53
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 51 publications
8
53
0
Order By: Relevance
“…This model is in accord with previous reports indicating that MYC activates transcription of TERT and other target genes after Pol II engagement, possibly by stimulating Pol II C-terminal domain phosphorylation and/or promoter clearance or elongation (8,17,20) and with recent studies indicating a role of yeast SAGA in transcription elongation (12,27,76,78). Similarly, Mediator has also been shown to play a role postrecruitment of Pol II during the initiation phase of transcription in mouse cells (74), stimulates TFIIB recruitment and initiation/reinitiation in vitro (2,45,85), and physically and/or functionally associates with various elongation factors, including TFIIS (76), Brd4/P-TEFb (84), and DSIF (46), and with coding regions of yeast genes (1,87). Clearly, it will be important to identify the steps downstream of TFIID/Pol II loading that are controlled by STAGA and core Mediator on the TERT promoter and the detailed activation mechanisms involved.…”
Section: Discussionsupporting
confidence: 74%
“…This model is in accord with previous reports indicating that MYC activates transcription of TERT and other target genes after Pol II engagement, possibly by stimulating Pol II C-terminal domain phosphorylation and/or promoter clearance or elongation (8,17,20) and with recent studies indicating a role of yeast SAGA in transcription elongation (12,27,76,78). Similarly, Mediator has also been shown to play a role postrecruitment of Pol II during the initiation phase of transcription in mouse cells (74), stimulates TFIIB recruitment and initiation/reinitiation in vitro (2,45,85), and physically and/or functionally associates with various elongation factors, including TFIIS (76), Brd4/P-TEFb (84), and DSIF (46), and with coding regions of yeast genes (1,87). Clearly, it will be important to identify the steps downstream of TFIID/Pol II loading that are controlled by STAGA and core Mediator on the TERT promoter and the detailed activation mechanisms involved.…”
Section: Discussionsupporting
confidence: 74%
“…The original system was reconstituted from homogeneous preparations of Pol II, GTFs, and PC4. Purified Mediator [either intact TRAP/SMCC (20,21) or PC2, the form that mainly lacks the TRAP240/MED13-TRAP230/MED12-CDK8-CycC subcomplex (13,22)] could be shown to potentiate both basal and activated transcription. Similarly, in a Mediator-depleted nuclear extract system, Mediator dependence of basal and activated transcription was readily demonstrable (10,12,14,17).…”
Section: Differential Mediator-and Tfiib-responsiveness Of Crude and mentioning
confidence: 99%
“…Importantly, in contrast to chromatin coactivators, Mediator can facilitate DNA-templated transcription, and thus acts relatively late in the overall activation pathway on natural templates (8). Several lines of evidence suggest that Mediator function is manifested both at the level of the initial establishment of the PIC as well as its postrecruitment function (5,7,(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies in yeast have revealed that the CDK8 module is associated with Mediator complexes in the genome upstream of active genes (2) and is essential for efficient transcriptional activation by both the Gal4 and Sip4 activators (19,24,57). Similarly, human Mediator complexes containing the CDK8 module are clearly recruited to target gene promoters in an activator-dependent manner both in vitro and in vivo and appear to promote, and in some cases are essential for, transcriptional activation (6,9,10,16,20,28,39,(58)(59)(60). Interestingly, CDK8 can specifically phosphorylate the CTD of Pol II (18,26,41,42,48), and CDK8 kinase activity in yeast specifically promotes Pol II transcription as well as the formation of a transcription reinitiation scaffold complex (26).…”
mentioning
confidence: 99%